(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In this article we can see observation of the developing projects based on tourism and its impact to Uzbekistan society. Tourism is an information-rich field, in which the collection, transmission, analysis and storage of information play an important role in decision-making at all levels of the field. In this regard, the formation and development of the project is of great importance for tourism activities, in which the latest information and communication technologies are actively used